Revaluation as a Model of Subsequent Measurement of Property, Plant, and Equipment – Case of Croatia - Mirjana Hladika; Danimir Gulin; Ivana Bernat (Croatian Economic Survey, 2021)
Accounting standards allow the application of two models for subsequent measurement of property, plant, and equipment, and those are the cost model and the revaluation model. The application of a certain model depends on the manager’s choice of accounting policy. The main goal of this paper is to investigate the application of the revaluation model for subsequent measurement of property, plant, and equipment in Croatian companies. Further goals are to examine how the fair value for revalued assets is determined, and what the level is of disclosed information about the determined fair value and the revaluation. The theoretical part of the paper analyzes different models for measurement of property, plant, and equipment, the issue of determining fair value, and disclosure requirements according to national and international accounting standards. The empirical part of the paper is conducted on 500 large and medium-sized Croatian companies from the service (utilities), production, and tourism sectors. Particular attention is placed on the notes to the financial statements of these companies. The research covers the period from 2014 to 2018. Collected data are analyzed by using descriptive statistics methods, point-biserial correlation, and Pearson correlation coefficient.